2014
DOI: 10.1097/meg.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of daily energy expenditure and health-related physical fitness parameters in patients with cholelithiasis

Abstract: Our results suggest that daily physical activity and muscle strength were impaired in female cholelithiasis patients when compared with the healthy controls. We suggest that using daily exercises, including not only aerobic but also strength training as lifestyle modifications in cholelithiasis patients, might be helpful for the development of more beneficial illness management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Our cross-sectional study confirmed this finding. However, Celikagi et al [14] recently reported that objectively measured maximal aerobic capacity from the Astrand submaximal exercise protocol was not significantly different between 30 female patients with cholelithiasis (VO2max in ml/kg/min: 21.2±6.3) and 30 healthy controls women (VO2max in ml/kg/min: 22.3±4.4) ( P =.55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cross-sectional study confirmed this finding. However, Celikagi et al [14] recently reported that objectively measured maximal aerobic capacity from the Astrand submaximal exercise protocol was not significantly different between 30 female patients with cholelithiasis (VO2max in ml/kg/min: 21.2±6.3) and 30 healthy controls women (VO2max in ml/kg/min: 22.3±4.4) ( P =.55).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study used self-reported 10 km race performance as the indicator of CRF. Another small sample study reported that aerobic capacity (measured by Åstrand submaximal exercise) was not significantly different between women with cholelithiasis and women who were healthy [14]. Therefore, in the present study, we examined the prevalence of gallbladder disease across levels of CRF, objectively measured by maximal treadmill exercise test, based on the database of the Aerobics Center Longitudinal Study (ACLS).…”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition, decreased grip strength and SMM, as the key components of frailty or sarcopenia, were reported to be more prevalent and associated with worse prognosis in individuals with Crohn’s disease, ulcerative colitis, celiac disease, pancreatitis, and gallbladder and biliary disease. 22 , 23 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure, mm Hg Systolic 119 (14) 123 (14) 120 (14) 118 (14) <.001 Diastolic 81 (10) 83 (10) 81 (10) 78 (9) <.001…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…However, the study used selfreported 10 km race performance as the indicator of CRF. Another small sample study reported that aerobic capacity (measured by Åstrand submaximal exercise) was not significantly different between women with cholelithiasis and women who were healthy [14]. Therefore, in the present study, we examined the prevalence of gallbladder disease across levels of CRF, objectively measured by maximal treadmill exercise test, based on the database of the Aerobics Center Longitudinal Study (ACLS).…”
Section: Introductionmentioning
confidence: 99%